Immunomodulator effect of Robusta Lampung coffee extract (Coffee Canephora Var Robusta) in layer chicken infected with Salmonella enteritidis bacteria - Dahliatul Qosimah; Djalal Rosyidi; Lilik Eka Radiati; Indah Amalia Amri; Dodik Prasetyo; Fajar Shodiq Permata; Ma A Guiang Beltran; Aulanni’am Aulanni’am; Agri Kaltaria Annisa (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2020)
Salmonellosis that attacks poultry, caused by Salmonella enteritidis is a cause of food borne disease in zoonotic humans. Treatment of this disease uses antibiotics but if used irrationally it can result in the emergence of multi-drug resistant bacteria. At present many treatments use herbs which are considered to reduce the negative effects of antibiotics and are environmentally friendly, one of which is coffee. Green coffee is considered to have many active ingredients such as chlorogenic acid (CGA), alkaloids, tannin, polyphenols and polysaccharides which are useful as antimicrobial, anti-inflammatory and enhances the body's immune system. The study used 60 heads ISA Brown day-old chicks (layer strain) chickens artificially infected with S. enteritidis bacteria with concentration of 108 CFU/ml, consisting of negative controls (healthy chickens, without coffee, positive control (chickens were given), T1, T2 and T3 was given different doses of coffee extract with 500 mg/kg BW, 1000 mg/kg BW and 1500 mg kg BW, respectively. The treatments with coffee extracts were given on days 3-15, then infected with 0.5 ml bacteria on day 16 and 60 chickens were necropsied at day 18 for histopathology. Data on relative levels of CD8 Tc cells were calculated using the flowcytometer test and analyzed quantitatively using the One Way ANOVA with a confidence level of 95% while the jejunum histopathology was observed using a microscopy and analyzed descriptively. Results showed that Robusta coffee extract from Lampung can act as an antibacterial by increasing CD8 + T cells and repairing jejunum histopathology